Implementation of Contextual Teaching and Learning Model on History Lesson to Improve Student’s Historical Thinking Skill - Sitorus, Margaretha Setiona Marisi; Syaiful Amin; Abu Hasan Ali (Journal of Practice Learning and Educational Development, 2026)
The purpose of studying history for students is not limited to only understanding the what, who, and how aspect in history events. Through history, students need to understand the meaning of it and what does it has to do with their life in the present time. Contextual Teaching and Learning (CTL) model provide a real-life example as a context to their history study, thus, this model can improve their historical thinking skills since they can find the meaning of studying history and what it has to do in their life by themself. This study aims to understand how SMA Negeri 11 Semarang use Contextual Teaching and Learning (CTL) in history lesson to improve student’s historical thinking skills through study case method at Abu Hasan Ali, S.Pd.Gr’s history class. With Contextual Teaching and Learning (CTL) model, students can take part actively in their own study so they can understand the meaning of history and it correlation to their life. And through it, they also improve the skills that included in historical thinking skill such as think diachronically, synchronically, causally, interpretively, multi-perspectively, reflectively, critically, creatively, and contextually.